How Affective Polarization Shapes Americans' Political Beliefs: A Study of Response to the COVID-19 Pandemic. Issue 3 (24th August 2021) - Druckman, James N.; Klar, Samara; Krupnikov, Yanna; Levendusky, Matthew; Ryan, John Barry
Abstract: Affective polarization – partisans' dislike and distrust of those from the other party – has reached historically high levels in the United States. While numerous studies estimate its effect on apolitical outcomes (e.g., dating and economic transactions), we know much less about its effects on political beliefs. We argue that those who exhibit high levels of affective polarization politicize ostensibly apolitical issues and actors. An experiment focused on responses to COVID-19 that relies on pre-pandemic, exogenous measures of affective polarization supports our expectations. Partisans who harbor high levels of animus towards the other party do not differentiate the "United States'" response to COVID-19 from that of the Trump administration. Less affectively polarized partisans, in contrast, do not politicize evaluations of the country's response. Our results provide evidence of how affective polarization, apart from partisanship itself, shapes substantive beliefs. Affective polarization has political consequences and political beliefs stem, in part, from partisan animus.